Multi-energy cooperative utilization business models: A case study of the solar-heat pump water heater. (July 2019) - Li, Zhuoran; Ma, Linwei; Li, Zheng; Ni, Weidou
Abstract: In China today, as well as other areas of the world, new technologies that apply multi-energy cooperative utilization and seek commercialization face the challenge of economic uncertainty. In this context, business models have a significant influence on the techno-economic performance of the technology projects. By using the solar-heat pump water heater as a case study example, the aim of this study is to develop a techno-economic model to evaluate and compare the techno-economic performance of multi-energy cooperative utilization under different business models to be able to recommend steps for improved commercialization going forward. The results indicate that in the model called "no third party intervention, " where the transaction is solely between a single enterprise operator and the user, the investment value of this technology is weak from the user's point of view. Therefore, government incentive is needed at a high ratio of subsidy to entice the user to purchase it (or this technology). When energy service companies become involved in the transaction, third party firms that purchase the products and basically lease them to customers not only avoid any high initial investment cost but also improve the economics of the project by receiving additional value-added services. In this circumstance, only a reasonable government subsidy is needed and then, the project has an investment value and benefits for all stakeholders which are involved. Highlights: Today, multi-energy cooperative utilization technologies face economic challenges. We evaluate and compare techno-economic performance under different business models. We use the solar-heat pump water heater as a case study example. The effective business model includes third party energy service companies. Third party involvement means users avoid initial costs and the economics improve.